AB0094 Migration, colonization and distribution of bone marrow mesenchymal stem cells transplanted in cia rats were traced by green fluorescent protein. (15th June 2017) - Hou, J; Xu, K; Zhang, L; Zhang, G; Gao, J; Ma, D; Fan, J
Abstract : Background: The mechanism of mesenchymal stem cells involved in injury and repair in vivo is not fully understood, so it is difficult to evaluate the effect of stem cells on rheumatoid arthritis. Objectives: To investigate the migration, colonization and distribution of bone marrow mesenchymal stem cells (BM-MSCs) traced by green fluorescent protein (GFP) in the immune organs and joints of CIA rats, and study the mechanism of MSCs in repairing damage. Methods: 1.MSCs labeled with GFP was cultured, amplified and identified in vitro. 2.Injected with mixture of II type collagen and complete Freund's adjuvant into Wistar rats space at 14 days: It was randomly divided into five groups, including early intervention group (n=20), late intervention group (n=20), CIA early control group (n=12), late control group (n=12) and normal control group (n=12).(2) MSCs were injected from tail veins according to the number of 1×10 7 /kg, and the control groups were given equal volume of normal saline. (3) Observe the changes of arthritis index, arthritis swelling degree, and appearance of imageology and pathology. 3.The spleen, thymus, lymph nodes and joint tissues of the rats were made into pathological sections when transplanted at 3, 11, 30 and 42 days.The migration and distribution of the transplanted cells in the immune organs and the inflammatory joints were detected by immunohistochemistry. Results: 1.(1)The arthritis index and degree of joint swelling in early and later intervention groups were decreased significantly than that of CIA control groups (P<0.05). (2)The early intervention group had lower arthritis index and the degree of joint swelling than the later intervention group (P<0.05). 2.The positive results of GFP was successfully detected by immunohistochemical method in the immune organs and joints of CIA rats, and sustainable for at least 42 days. Conclusions: 1.MSCs transplanted through tail vein can migrate to the spleen, lymph nodes and thymus and joints, and can be long-term (42 days) colonization in these organizations. 2.The intervention of MSCs for CIA rats was effective, and early intervention effect was better than advanced intervention. References: Gordon I. A. MacDonald, Andrea Augello, Cosimo De Bar. Role of mesenchymal stem cells in reestablishing immunologic tolerance in autoimmune rheumatic diseases. Arthritis &Rheumatism. 2011 Spe, 63(9): 2547–557. David Guéit, Marie Maumus, Florence Apparailly, Christian Jorgensen & Danièe Noë.Therapeutic mesenchymal stem or stromal cells in rheumatic diseases: rationale, clinicaldata and perspectivesClinical. Investigation. 2011 Sep, 1(9): 1269–1277. Disclosure of Interest: None declared